Modeling Learning Strategy for Students with Competitive Behavior and its Impact on Civic Education Learning Achievement - Evi Susilawati (Proceedings of AICS - Social Sciences, 2017)
A good and effective learning process requires arts, skills and knowledge so that the learning strategies undertaken by the teachers meet the learning objectives to be achieved. Likewise in learning Civic Education where the expertise of teachers in determining the right learning strategy depends on student learning outcomes. This research is quasi experiment by implementing the curriculum 2013 lesson plan of modeling and conventional learning. Cognitive domain test and competitive behavior questions were used in this study as instrument. Six indicators of competitive behavior are weak communication, negative perceptions, no division of labor, disagreements, self-oriented, use tactics coercion. This study was conducted in the seventh grade students of SMP Negeri I Labuhan Deli of Deli Serdang. North Sumatra Province where class VII-3 as experimental class and class VII-5 as control class. The finding showed that students who behave competitively if taught by using modeling learning strategy get lower the result of studying Civic Education than the students taught by using conventional learning strategy.